Efficacy of Teaching Recovery Techniques (TRT) on Psychological Functioning of Flood Affected Girls in Pakistan - Saadia Dildar, and Rukhsana Kausar , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The current experimental study investigated the efficacy of Teaching Recovery Techniques (TRT) on the psychological functioning of the adolescent girls who witnessed September 2014 flood in Central Punjab (Hafizabad and Jhang districts), Pakistan. The adolescent girls (M= 14.27, SD= .98) were selected from government schools of flood affected areas and assigned randomly to the experimental and wait control groups. The measures included Urdu translated scales of Children’s Revised Impact of Event Scale-13, Depression Self Rating Scale, Post-trauma Cognitions Inventory-Children, Trauma Memory Quality Questionnaire. The experimental and wait control groups were pre-assessed on the mentioned scales. The groups which met criteria of posttraumatic stress symptoms severity (cut off=>30), were subsequently randomly assigned to experimental and control groups. Then experimental groups in both districts were given TRT separately by trained professional and a facilitator, however, control group was kept waiting till the treatments ended and post assessment was done. Independent sample t-test and paired sample t-test revealed significant differences existed across the groups for pre and post measures of the study variables. Experimental group had reduced posttrauma memory, decreased negative cognitions and PTSS severity as compared to wait control group after TRT. Findings are implicated for counseling and psychological rehabilitation of the flood affected adolescents.